2020
DOI: 10.1007/s10584-020-02691-9
|View full text |Cite
|
Sign up to set email alerts
|

Climate humanitarian visa: international migration opportunities as post-disaster humanitarian intervention

Abstract: With global action being outpaced by climate change impacts, communities in climate-vulnerable countries are at increased risk of incurring climate-induced losses and damages. In the last few years, disasters from extreme weather events such as typhoons have increased and have breached records, with typhoon Haiyan being the strongest ever typhoon to make landfall. Such an event solicited global compassion and altruism where Canada and the USA, apart from doling out traditional humanitarian aid, also offered im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…And more than symbolic recognition of their worth, it would include amnesty for irregular migrants, wraparound resettlement support (cf. Farbotko et al, 2022; McClain et al, 2022), funding for community initiatives, and legal options for accessing permanent residency (e.g., Farbotko et al, 2022; Heyward & Ödalen, 2016; Matias, 2020; McCarney & Kent, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…And more than symbolic recognition of their worth, it would include amnesty for irregular migrants, wraparound resettlement support (cf. Farbotko et al, 2022; McClain et al, 2022), funding for community initiatives, and legal options for accessing permanent residency (e.g., Farbotko et al, 2022; Heyward & Ödalen, 2016; Matias, 2020; McCarney & Kent, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One striking key finding from the analysis is that the literature following the Foresight Report overwhelmingly located trapped populations in South America [e.g., in Guatemala (Afifi et al, 2015;Milan & Ruano, 2014), Peru (Adams, 2016), and Colombia (Matias, 2020)], Africa [e.g., in Morocco (Sow et al, 2015), Ghana (Hillmann & Ziegelmayer, 2016), Senegal (Zickgraf, 2019), Zambia (Nawrotzki & DeWaard, 2018), Ethiopia (Hermans & Garbe, 2019), and Burkina Faso (Gray & Wise, 2016)], as well as in the Middle East (Geddes, 2015), and Asia (Bhatta et al, 2015), including Vietnam (Warner & Afifi, 2014), Bangladesh (Ayeb-Karlsson, 2020bPenning-Rowsell et al, 2013), Indonesia (McCaughey et al, 2018, and Tajikistan (Blondin, 2020). At the same time, none of the study samples identified involuntarily immobile populations in Europe or Australia, while the articles placing them in the US referred mainly to Afro-Americans (Figure 1).…”
Section: The Geography Of the "Trapped" Figurementioning
confidence: 99%
“…Disasters and climate change can have a significant impact on migration and displacement. Climate change is causing extreme weather conditions and rising sea levels, which can lead to displacement and migration [27]. Disasters such as floods, storms, and drought can cause people to flee their homes to seek safety elsewhere.…”
Section: Environmental Impactmentioning
confidence: 99%